Integrating hypertension and diabetes management in primary health care settings: HEARTS as a tool - David Flood; Elizabeth W. Edwards; David Giovannini; Emily Ridley; Andres Rosende; William H. Herman; Marc G. Jaffe; Donald J. DiPette (Pan American Health Organization, 2022)
Hypertension and diabetes are modifiable cardiovascular disease (CVD) risk factors that contribute to nearly one-third of all deaths in the Americas Region each year (2.3 million deaths). Despite advances in the detection and clinical management of hypertension and diabetes, there are substantial gaps in their implementation globally and in the Region. The considerable overlap in risk factors, prognosis, and treatment of hypertension and diabetes creates a unique opportunity for a unified implementation model for management at the population level. This report highlights one such high-profile effort, the Pan American Health Organization's "HEARTS in the Americas" program, based on the World Health Organization's HEARTS Technical Package for Cardiovascular Disease Management in Primary Health Care. The HEARTS program aims to improve the implementation of preventive CVD care in primary health systems using six evidence-based, pragmatic components: Healthy-lifestyle counseling, Evidence-based protocols, Access to essential medicines and technology, Risk-based CVD management, Team-based care, and Systems for monitoring. To date, HEARTS implementation projects have focused primarily on hypertension given that it is the leading modifiable CVD risk factor and can be treated cost-effectively. The objective of this report is to describe opportunities for integration of diabetes clinical care and policy within the HEARTS hypertension framework. A substantial global burden of disease could be averted with integrated primary care management of these conditions. Thus, there is an urgency in applying lessons from HEARTS to close these implementation gaps and improve the integrated detection, treatment, and control of diabetes and hypertension.